Sex Differences in Health Behaviors of Austrian Teachers and School Principals - Tanous, Derrick R.; Motevalli, Mohamad; Wirnitzer, Katharina (International Journal of Population Data Science, 2022)
Introduction Currently, about 2% of the European working population ( 5 million people) are teachers, who are a characterized occupational group with various roles as educators, partners, counselors, social directors, professional managers, and political theorists. Teachers’ health has a remarkable effect on teaching quality, and consequently, on the success of students of future generations. Public and occupational health are highly related to lifestyle behaviors (including diet type and PA); however, little is known regarding lifestyle patterns in different groups of teachers, particularly males and females. This study aimed to investigate sex differences in health/lifestyle behaviors of Austrian secondary-level teachers and school principals. Methods This cross-sectional and multidisciplinary study is a part of the bigger Austrian-wide research project From Science 2 School (www.science2.school/en; supported by Federal Ministry of Education, Science, and Research). A sample size of 89,243 teachers and principals from 2,554 secondary schools (level I & II) were invited to participate, and a total number of 1,350 teachers and principals (1.5% of eligible Austrian participants; aged 45.8±11.4; 69.7% females) completed an online survey. In addition to sociodemographic information, a complete profile of lifestyle behaviors (e.g., diet type: omnivorous, vegetarian, vegan; nutritional patterns; exercise and sports activities; smoking habits; and alcohol consumption) was evaluated. Findings Male teachers were 2.1 years older than females (p<0.01). While there was no sex difference in leisure-time sports participation (p>0.05), males engaged in club sports more than females (39.1% vs. 24.9%; p<0.01). The frequency of sports/exercise engagement was higher in males compared to females (3.1 ± 1.5 vs. 2.9 ± 1.4; p=0.02). Omnivorous diet was significantly more common in male teachers (93.9% vs. 87.2%; p<0.01), while a vegetarian diet was significantly more prevalent in females compared to male teachers (9.8% vs. 3.4%; p<0.01). There was no significant difference between male and female teachers in the prevalence of vegan diet (p>0.05). Conclusion Despite some differences in lifestyle components between females and males, teachers in both sexes appeared to have a healthier lifestyle compared to general populations reported by similar investigations. This finding might be associated with the higher educational level of teachers, particularly their improved individual capabilities (including knowledge, skills, competencies, values, and qualifications) and social advantages (e.g., networks, general living conditions) to implement toward scientifically well-accepted healthy behaviors. This study can serve as a starting point for future health-related interventions focusing on sex differences in the dual approach of “healthy eating – active living” considered the practical recommendation to achieve sustainable health.